Level of road user satisfaction with safety and confort on jalan Mohammad hatta - Chitra Utary,; Muh Akbar,; Dhea Riski Amanda, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Mohammad Hatta Road is a type of district road that is used as a link between Kurik District and MalindiMalindiMalindi District. The increased activity and mobility of residents on Jalan Mohammad Hatta have not been balanced with safety and comfort for road users, such as damage to the road body and a lack of supporting facilities on the road. The purpose of this study was to determine the factors that influence the lack of safety and comfort levels of road users and the influence between satisfaction variables on safety and comfort variables on Jalan Mohammad Hatta. This research method uses the correlation test method. This test is used to find the relationship between variable X (satisfaction) and variable Y (safety and comfort) on Jalan Mohammad Hatta which has bad road conditions. The data used in this study were obtained by distributing questionnaires with a total sample of 394 respondents. The results of this study showed that people were dissatisfied a percentage of 83.61%, insecure with a percentage of 83.92%, and very uncomfortable with percentage of 84.01%, in terms of several factors, namely road conditions, stability of vehicles, health, travel effectiveness, economy, pavement structure, socio-cultural conditions, facilities, and accessibility. There is a relationship between the satisfaction variable and the safety variable with a correlation value of 0.905 and a relationship between the satisfaction variable and the comfort variable with a correlation value of 0.886. So it shows that the higher the level of safety and comfort, the higher the level of satisfaction of road users.